Transaksi Pasar Mata Uang (Foreign Exchange) Dalam Perspektif Fiqh Islam - Huda, Bakhrul (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The article discusses the mechanism of foreign exchange through what so-called Forex teamster. The study concludes that trading, viewed from the aspect of goods exchanged, consists of three kinds, namely barter, buying and selling of goods with money, and money exchange. It is allowed to use brokerâs service in money exchange activity. It has been even a compulsory (wÃ¢jib âayn) for a trader to select and chose a legal and trusteed broker in order to assure and secure his money. The reason is that a broker becomes not only wakÃ®l (a trustee or an agent) of trader to proceed the transaction of the trader into the market, but also plays role as a responsible person who guarantees the trustiness of market over the trader. In other words, a broker has to make the market trusts every traderâs transaction. The transaction has to cover all benefits and risks. It can be understood, therefore, that non-dealing desk broker is a person who meets the requirements of wakÃ¢lah and damÃ¢n contacts implemented within Forex transaction.